2009
DOI: 10.1080/0972060x.2009.10643703
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Distillation-Extraction, Hydrodistillation and Static Headspace Methods for the Analysis of Volatile Secondary Metabolites ofAlpinia zerumbet(Pers.) BurttetSmith. from Southeast Brazil

Abstract: Alpinia zerumbet (Zingiberaceae) is cultivated in several tropical areas. It has a high value all over the world as a spice in culinary preparations and for its medicinal properties. The composition of the essential oil obtained by simultaneous distillation-extraction (SDE) and hydrodistillation (HD) from fresh leaves of A. zerumbet was analyzed by GC-MS. In both samples the main constituents were terpinen-4-ol, 1,8-cinole, sabinene and γ-terpinene together with caryophyllene and caryophyllene oxide sesquiterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 16 publications
1
26
2
Order By: Relevance
“…The main constituents were terpinen-4-ol, 1,8 cineole and γ-terpinene (Table 1, Figure 1) (Victório, 2008;Victório et al, 2009a). These constituents were found in studies on the essential oil from other samples of A. zerumbet (Zoghbi et al, 1999;Ali et al, 2002;Elzaawely et al, 2007;Victório et al, 2009b). Caryophyllene oxide was also found in low amounts (Figure 1).…”
Section: Resultsmentioning
confidence: 93%
“…The main constituents were terpinen-4-ol, 1,8 cineole and γ-terpinene (Table 1, Figure 1) (Victório, 2008;Victório et al, 2009a). These constituents were found in studies on the essential oil from other samples of A. zerumbet (Zoghbi et al, 1999;Ali et al, 2002;Elzaawely et al, 2007;Victório et al, 2009b). Caryophyllene oxide was also found in low amounts (Figure 1).…”
Section: Resultsmentioning
confidence: 93%
“…Mpalantinos et al (1998) suggested that flavonoids and kavapyrones are responsible for vasodilator activity of aqueous extracts of A. zerumbet, while Lahlou et al (2003) attributed it to some essential oil constituents therapeutic effects of A. zerumbet. A similarity between Alpinia purpurata and A. zerumbet was found in phytochemical studies, in terms of essential oils and flavonoids composition (Victório, 2008;Victório et al, 2009b). The presence of flavonoids supported evidence for the chemosystematic features of the Zingiberiflorae, Zingiberaceae family (Pugialli et al, 1993;Victório et al, 2009b).…”
Section: Introductionmentioning
confidence: 77%
“…Alpinia zerumbet, known as 'colônia', is widely used in northeastern and southeastern Brazil as infusions or decoctions for treatment of arterial hypertension. Hypotensive effects of this species have been justified by composition of hydroalcoholic and aqueous extracts and essential oils Victório et al, 2009a). According to Mendonça et al (1991) a decrease blood pressure in rats and dogs was observed using hydroalcoholic extracts of A. zerumbet.…”
Section: Introductionmentioning
confidence: 99%
“…In the essential oil of A. purpurata, α-pinene, β-pinene and 1,8 cineol predominate in leaves and flowers. Sesquiterpenes β-caryophyllene and caryophyllene oxide are also common among this species (Zoghbi et al, 1999;Joseph et al, 2001;Mallavarapu et al, 2002;Victório et al, 2009e;2009f;2010b).…”
Section: Phytochemical Studiesmentioning
confidence: 99%